Phytochemical Analysis and Influence of Edaphic Factors on Lawsone Content of Lawsonia inermis L. - A. Kumar, B. Upadhyay*, A. K. Dhaker, K.P. Singh (Journal of Phytology, 2010)
SUMMARY Lawsonia inermis commonly called as Henna or Mehandi is known for its cosmetic properties, and is an important source of phytochemicals of immense medicinal and pharmaceutical potential. Present study was carried out to study the influence of idaphic factors on quantitative estimation of lawsone content and morphology of leaves in Henna leaves collected from different region of Rajasthan in different season. Phytochemical analysis shows that October-November season crop leaves show good quality Henna compare to others. The Phytochemical analysis was also carried out to study the presence of different Phytochemicals in Lawsonia inermis.Â Lawsone, the active ingredient in the leaves, responsible for color production in Lawsonia inermis was also estimated in different plant samples. <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Upadhyay, B. et al. Phytochemical Analysis and Influence of Edaphic Factors on Lawsone Content of Lawsonia inermis L. <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">J Phytol 2/6 (2010) 47-54.